Morphometric analysis of furcation anatomy of Maxillary and mandibular first molars in South indian population - DAYANAND JOHN VICTOR; PRAKASH PONNUDURAI SAMUEL GNANA; VINOTH THEAGARAJAN; SANGEETHA SUBRAMANIAN (International Journal of Pharma and Bio Sciences, 2017)
This study has been sketched and formatted to measure and analyze the furcation anatomy of maxillary and mandibular first molars in a South Indian population, so as to assess if specific changes in the furcal anatomy, could predispose these teeth for morbidity associated with periodontal disease. The experimental sample consisted of 90 (maxillary and mandibular molars) that were extracted due to periodontal disease. The root surfaces were viewed through a 2.5X surgical loupe. The buccal, mesial, distal and lingual surfaces of each tooth was evaluated using a Labomed CZM4 4:1 Stereozoom Microscope. Degree of separation at the point of furcation was calculated using a Image – Pro Plus Software version 6. Mean± standard deviation of different root surface measurements for root trunk length were recorded form axillary and mandibular first molars. Similarly, mean± standard deviation of distance of the fluted area from the CEJ (Cemento-enamel Junction), degree of separation at the point of furcation were also recorded. Statistically significant differences were found between all measured parameters for buccal, mesial and distal surfaces (p <0.0001, paired t test) in maxillary first molars and buccal & lingual surfaces (p<0.0001 and < 0.002, paired t test) in mandibular first molars. Correlation of the study results with other studies, revealed significant differences in the furcal anatomy in this study population, on comparison with other published studies. The study also discusses its clinical significance.